Das Wiener Kärntnertortheater 1728–1748: Vom Städtischen Schauspielhaus zum Höfischen Opernbetrieb Andrea Sommer-Mathis and Reinhard Strohm, eds Vienna: Hollitzer, 2023 - Forment, Bruno 1978- (2024)
Review of a book edited by Reinhard Strohm and Andrea Sommer-Mathis
FRIS
1
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Theater; Opera seria